Religious Guidance to Improve Elderly Individuals’ Understanding of the Islamic Religion - Eka Sriwahyuni (Nalar: Journal of Pedagogy and Society, 2021)
This field research aims to examine this problem and explore scientifically about religious development to improve religious understanding of the elderly in the technical implementation unit of social services, Tresna Werdha Husnul Khotimah, Riau Province Social Service. To obtain data in accordance with research purposes, the authors used three data collection methods including observation, interviews, and documentation. After the data is collected, it will be analyzed using qualitative descriptive techniques with steps including data reduction, data display, and conclusion drawing after first going through the process of testing the validity of the data. The results show that religious guidance to improve understanding of the Islamic religion of the elderly in the technical implementation unit of social services tresna wherda husnul khotimah Riau Province social service is categorized as good implementation.